MOYENS D’EXPRESSION DE LA POSSESSION INALIÉNABLE DANS LES CONSTRUCTIONS VERBALES AVEC DES NOMS DE PARTIES DU CORPS (DOMAINE FRANÇAIS-ROUMAIN) - DINCĂ, Daniela; BĂDESCU, Ilona (Studia Universitatis Babeș-Bolyai Philologia, 2022)
Means of Expressing Inalienable Possession in Verb Structures with Body Part Nouns (French and Romanian). Departing from the verb structures with the possessive dative that express the inalienable possession between a noun that names body parts (Nbp) and its possessor in Romanian (Ro: I-a rupt gâtul. / Fr. Il lui a rompu le cou), we set out to establish a typology of verb structures consisting of two subclasses: (1) Verbs that place the possessor in the possessive dative and the Nbp in the accusative (direct object); (2) verbs that place the Nbp as an adverbial modifier and the possessor in the possessive dative, possessive accusative or genitive. The second objective of our study is to carry out a comparative-based analysis of the ways of expressing the inalienable possession in the verb structures of the two Romance languages, constructed with the lexeme Fr. cou, gorge / Ro gât, to highlight the similarities and differences in this relationship-type structures specific for the two Romance languages. For the analysis we resorted to an authentic corpus, complied from real-life examples sampled from journalistic texts (Corpus Leipzig, online newspapers), supplemented by electronic dictionaries (TLFi, CNTRL, Dex online). Given the richness of verb structures and the considerable number of differences between the two languages, we systematised our analysis in several stages: (1) identifying the verb structures built with the possessive dative; (2) establishing a verb structure typology according to the syntactic function assigned to the Nbp (subject, direct object, indirect object, adverbial modifier) and its possessor (possessive dative, possessive accusative, genitive); (3) highlighting the similarities and differences between the two languages in terms of the construction of the inalienable possession relationship between the Nbp and its possessor. Article history: Received 28 June 2022; Revised 29 October 2022; Accepted 15 November 2022; Available online 20 December 2022; Available print 30 December 2022. REZUMAT. Mijloace de exprimare a posesiei inalienabile în construcțiile verbale cu nume de părți ale corpului (domeniu francez-român). Pornind de la construcțiile verbale din limba română cu Dativ posesiv care exprimă posesia inalienabilă între obiectul posedat, un substantiv parte a corpului (Spc), și posesorul său (Roum : I-a rupt gâtul. / Fr. Il lui a rompu le cou), articolul de față își propune să realizeze o tipologie a construcțiilor verbale care pot fi repartizate în două clase: (1) Verbe care distribuie posesorul în Dativ posesiv și Spc în Acuzativ (complement direct); (2) Verbe care distribuie Spc în funcția de complement prepozițional / circumstanțial și posesorul în Dativ posesiv, Acuzativ posesiv sau Genitiv. Al doilea obiectiv al studiului nostru este acela de a realiza o analiză comparativă a modalităților de exprimare a posesiei inalienabile în structurile verbale din cele două limbi construite cu lexemul fr. cou, gorge / roum. gât pentru a pune în evidență asemănările și deosebirile în construirea acestei relații în cele două limbi romanice. Corpusul pe care se bazează acest studiu este autentic, fiind format din exemple atestate în texte jurnalistice (Corpus Leipzig, ziare online), sau preluate din dicționare electronice (TLFi, CNTRL, Dex online). Având în vedere bogăția construcțiilor verbale și numărul mare de diferențe dintre cele două limbi, am organizat analiza noastră în mai multe etape: (1) identificarea structurilor verbale construite cu Dativul posesiv; (2) realizarea unei tipologii a construcțiilor verbale plecând de la funcțiile sintactice ale Spc (subiect, complement direct, complement indirect, complement prepozițional, complement circumstanțial de loc) și ale posesorului său (Dativ posesiv, Acuzativ posesiv, Genitiv); (3) punerea în evidență a asemănărilor și deosebirilor de exprimare a relației de posesie inalienabilă în cele două limbi. Cuvinte-cheie: dativ posesiv, posesie inalienabilă, nume de părți ale corpului (Npc), posesor, funcție sintactică